2015
DOI: 10.1680/jadcr.14.00078
|View full text |Cite
|
Sign up to set email alerts
|

Dry powder alkali-activated slag cements

Abstract: This paper reports on the results of an investigation into the possibility of producing dry powder alkali-activated slag cements as a ready-to-use product which can be packed in bags and mixed with water to produce a concrete. The cements were produced using a neutral granulated blast-furnace slag and sodium carbonate. To accelerate strength development at ambient temperatures, a combination of silica fume and slaked lime was used as accelerating admixture in the cement's formulation. Powder sodium lingosulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The production of hybrid cement requires less clinker than that for ordinary Portland cement, leading to a decrease in CO 2 emissions per tonne of hybrid cement manufactured. Hybrid alkaline cements is often preferred over their alkali activated counterparts because its hydration occurs at ambient temperature, and its production do not require the addition of highly alkaline chemicals, but rather rely on a safe source of alkali formed in situ (sodium hydroxide) to facilitate both the dissolution of any amorphous phases present in the source materials [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The production of hybrid cement requires less clinker than that for ordinary Portland cement, leading to a decrease in CO 2 emissions per tonne of hybrid cement manufactured. Hybrid alkaline cements is often preferred over their alkali activated counterparts because its hydration occurs at ambient temperature, and its production do not require the addition of highly alkaline chemicals, but rather rely on a safe source of alkali formed in situ (sodium hydroxide) to facilitate both the dissolution of any amorphous phases present in the source materials [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of serving the one-part Na 2 CO 3 -activated slag binders as practical cementing materials in general applications, recent studies are extensively focused on the use of auxiliary activators to accelerate the kinetics of alkali activation [ 23 , 24 , 25 , 26 , 27 , 28 ]. Kovtun et al [ 29 ] enhanced the 1 day compressive strength of Na 2 CO 3 -activated slag concretes cured at ambient temperature up to 25 MPa via the additions of slaked lime (Ca(OH) 2 ) and silica fume. Akturk et al [ 30 ] observed that only the 3% Ca(OH) 2 addition promoted the hardening of the pastes within 6.5 h. Wang et al [ 31 ] revealed that the CaO addition was beneficial for the formation of C-A-S-H. Gao et al [ 32 ] suggested that the initial reaction between Ca(OH) 2 and Na 2 CO 3 was effective in removing the CO 3 2− ions in the aqueous phase to enhance the alkalinity.…”
Section: Introductionmentioning
confidence: 99%